Burnout in Nursing Home Wound Care Nurses: The Role of Workplace and Individual Factors in a Multicenter Study - Giulia Moretti; Elena Ricci; Marco Bellini (Journal of Wound Research and Technology, 2026)
Background: Burnout among nursing home wound care nurses is an emerging concern due to complex wound management, emotional burden, staffing challenges, and increasing resident care needs. Aim: To examine burnout levels and associated workplace and individual factors among nursing home wound care nurses Approach: A multicenter cross-sectional study was conducted among 486 wound care nurses from 18 nursing homes in Italy between 1 January and 3 March 2026. Burnout was measured using the BAT-12. Workplace factors, individual characteristics, and personal resources were analyzed using descriptive statistics and linear mixed models Results: The mean BAT-12 burnout score was 2.31 (SD = 0.62). Of 486 wound care nurses, 341 (70.2%) had no burnout, 89 (18.3%) were at risk for burnout, and 56 (11.5%) were likely suffering from burnout; overall, 145 (29.8%) had clinically relevant burnout symptoms. In the final model, emotional burden (B = 0.119, p < 0.001) and work-life interference (B = 0.218, p < 0.001) were associated with higher burnout, while skill use (B = −0.091, p = 0.008), self-efficacy (B = −0.132, p = 0.001), and resilience (B = −0.104, p = 0.006) were protective. Conclusions: Burnout was common among nursing home wound care nurses and was associated with both workplace demands and individual resources, highlighting the need for integrated prevention strategies Implication for Nursing Practice: Nursing homes should reduce emotional burden and work-life interference while strengthening wound care nurses’ skill use, self-efficacy, resilience, and access to supportive work environment